A problemática da patenteabilidade de material genético humano no INPI: uma análise da técnica CRISPR no uso das edições genômicas como vetor de patente dos produtos biológicos humanos - Ariosi, Mariângela de Fátima (2025)
The present dissertation aims to analyze the patentability of products and processes derived from human biological material within the scope of the Brazilian National Institute of Industrial Property (INPI), in light of the development of gene-editing biotechnologies, particularly the CRISPR/Cas system. The research seeks to understand the ethical, legal, and economic boundaries imposed by Brazilian and international legislation on the protection of inventions involving the human genome, proposing a critical interpretation of the interaction between science and law in the context of human rights perspectives. Epistemological and practical questions are addressed regarding the protection of life and human dignity in the face of biotechnological progress, questioning the balance between encouraging innovation and preserving bioethical values. Structured in four concise chapters, the work covers specific concepts of genetics and intellectual property, surveys of case law, and domestic and international regulations. It also develops a comparative study of the U.S. and Chinese systems, culminating in two main analytical axes of the thesis. The first analytical axis examines, from a comparative perspective, the regime of patentability of human genomic biotechnologies in the United States and China, with reference to the European system, identifying criteria, practices, and institutional strategies that influence global innovation. The second analytical axis investigates the patentability of CRISPR applied to health in Brazil, contextualized within a global framework, highlighting national practices in patent filings for products and processes related to human bionegetics, with emphasis on the study of totipotent (stem) and pluripotent cells. To achieve these aims, the research adopts a methodology combining inductive and deductive approaches; it is qualitative and comparative, grounded in bibliographic and documentary review of scientific and legal sources (international treaties, and Chinese, U.S., and Brazilian legislation), complemented by patentographic analysis and a case study involving MartinLab, a national reference in oncological biotechnology, along with interviews with specialists in the field. The theoretical framework integrates the doctrine of intellectual property with fundamental and human rights, drawing upon authors who address bioethics, biotechnology, and the legal protection of the human genome, thus situating the discussion within the broader context of scientific sovereignty and social justice. The justification for this research lies in the need to strengthen the legal debate on the protection of human biological material, given the growing prominence of biotechnology in the global scenario and its impact on public health and sustainable development. As for the expected results, beyond producing an organized and well-founded study supported by reliable quantitative and qualitative data, approaching a biogenetic patent manual that provides information not only on the Brazilian patent system, but also on those of China and the United States, the thesis aims further. It is believed that this academic process may lead to a substantiated critique of the Brazilian biogenetic patent system, and, above all, to the establishment of a more critical perspective on the Industrial Property Law (LPI), including the proposal of drafting adjustments or interpretive suggestions based on successful international experiences in the field of biogenetics.